Assessing Gender Differences In Using Reading Strategies In Classroom - Anisa Putri; Suharni Suharni; Dian Mega Putri (Horizon, 2023)
ABSTRACTThis research is motivated by the use of reading strategies by English students based on gender in the classroom. The study used a survey research design involving 38 students of English education study program consisting of 15 male students and 23 female students. Data were collected using the Survey of Reading Strategies (SORS) questionnaire developed by Mokhtari and Sheory (2002). Data were analyzed using a survey and statistical test independent sample t-test was conducted to determine the differences between women and men. The results of the analysis using the independent sample t-test showed that there was no significant difference in all subscales of gender differences in the use of reading strategies. Thus, gender does not play a role in determining the reading strategy used.Keywords: Gender, English Students, Reading Strategy.